(untitled) (Journal of Parents and Teachers, 2016)
During the course 2015-16, the head of studies of Primary and Infant Education degree of Pontificia Comillas University proposed a One-Minute-Teacher contest. Theobjective was to show in a one-minute video some aspects of the teacher’s job.